Anesthetic Management of Brain-dead Adult and Pediatric Organ Donors: The Harborview Medical Center Experience. Issue 1 (6th January 2022) - Lele, Abhijit V.; Nair, Bala G.; Fong, Christine; Walters, Andrew M.; Souter, Michael J.
Abstract : Supplemental Digital Content is available in the text. Abstract : Introduction: The exposure of anesthesiologists to organ recovery procedures and the anesthetic technique used during organ recovery has not been systematically studied in the United States. Methods: A retrospective cohort study was conducted on all adult and pediatric patients who were declared brain dead between January 1, 2008, and June 30, 2019, and who progressed to organ donation at Harborview Medical Center. We describe the frequency of directing anesthetic care by attending anesthesiologists, anesthetic technique, and donor management targets during organ recovery. Results: In a cohort of 327 patients (286 adults and 41 children), the most common cause of brain death was traumatic brain injury (51.1%). Kidneys (94.4%) and liver (87.4%) were the most common organs recovered. On average, each year, an attending anesthesiologist cared for 1 (range: 1 to 7) brain-dead donor during organ retrieval. The average anesthetic time was 127±53.5 (mean±SD) minutes. Overall, 90% of patients received a neuromuscular blocker, 63.3% an inhaled anesthetic, and 33.9% an opioid. Donor management targets were achieved as follows: mean arterial pressure ≥70 mm Hg (93%), normothermia (96%), normoglycemia (84%), urine output >1 to 3 mL/kg/h (61%), and lung-protective ventilation (58%). Conclusions: During organ recovery from brain-dead organ donors, anesthesiologists commonly administer neuromuscular blockers, inhaled anesthetics, and opioids, and strive to achieve donor management targets. While infrequently being exposed to these cases, it is expected that all anesthesiologists be cognizant of the physiological perturbations in brain-dead donors and achieve physiological targets to preserve end-organ function. These findings warrant further examination in a larger multi-institutional cohort.